Prognostic significance of elongator protein 3 expression in endometrioid adenocarcinoma - Yi, Wang; Jun-Ichiro, Ikeda; ., Nur Rahadiani; Mamat, Suhana; Ueda, Yutaka; Tian, Tian; Enomoto, Takayuki; Kimura, Tadashi; Aozasa, Katsuyuki; Morii, Eiichi (Spandidos Publications, 2012)
Elongator protein 3 (ELP3), the catalytic subunit of the elongator complex of RNA polymerase II, is involved in various functions, including transcriptional elongation, chromatin modification and cytoskeletal regulation. In this study, ELP3 expression was immunohistochemically examined in normal uterus tissue and uterine endometrioid adenocarcinoma tissue. ELP3 was abundantly expressed in both the proliferative and secretory phases of the endometrial cycle. However, ELP3 expression levels varied among cases of endometrioid adenocarcinoma. In patients with endometrioid adenocarcinoma, a low ELP3 expression was correlated to a high T-factor (p=0.036), tumor stage (p=0.001), lymph node metastasis (p<0.001), resistance to chemotherapy (p=0.045), recurrence (p=0.004) and poor prognosis (p=0.003). Univariate and multivariate analyses revealed that a low ELP3 expression was an independent factor for poor prognosis. In conclusion, this is the first study to examine the clinical implications of ELP3 expression in cancer.